Size photometry and fluorescence imaging of immobilized immersed extracellular vesicles - Andreas Wallucks; Philippe DeCorwin‐Martin; Molly L. Shen; Andy Ng; David Juncker (Journal of Extracellular Vesicles)
Abstract Immunofluorescence analysis of individual extracellular vesicles (EVs) in common fluorescence microscopes is gaining popularity due to its accessibility and high fluorescence sensitivity; however, EV number and size are only measurable using fluorescent stains requiring extensive sample manipulations. Here we introduce highly sensitive label‐free EV size photometry (SP) based on interferometric scattering (iSCAT) imaging of immersed EVs immobilized on a glass coverslip. We implement SP on a common inverted epifluorescence microscope with LED illumination and a simple 50:50 beamsplitter, permitting seamless integration of SP with fluorescence imaging (SPFI). We present a high‐throughput SPFI workflow recording >10,000 EVs in 7 min over ten 88 × 88 µm2 fields of view, pre‐ and post‐incubation imaging to suppress background, along with automated image alignment, aberration correction, spot detection and EV sizing. We achieve an EV sizing range from 37 to ∼220 nm in diameter with a dual 440 and 740 nm SP illumination scheme, and suggest that this range can be extended by more advanced image analysis or additional hardware customization. We benchmark SP to flow cytometry using calibrated silica nanoparticles and demonstrate superior, label‐free sensitivity. We showcase SPFI's potential for EV analysis by experimentally distinguishing surface and volumetric EV dyes, observing the deformation of EVs adsorbed to a surface, and by uncovering distinct subpopulations in <100 nm‐in‐diameter EVs with fluorescently tagged membrane proteins.